Case Report: A Chlamydia psittaci pulmonary infection presenting with migratory infiltrates - Wang, Jundi; Zhu, Yurou; Mo, Qiongya; Yang, Yanfei (Frontiers in Public Health, 2022)
Community-acquired pneumonia is a public health problem in all countries in the world, with a broad range of causative agents and Chlamydia psittaci infection tends to be overlooked. Pulmonary migratory infiltrates are commonly seen in eosinophilic pneumonia, cryptogenic organizing pneumonia, etc. However, the association of chlamydia psittaci and pulmonary migratory infiltrates has been seldom described in literatures before. We reviewed a 64-year-old man referred to our hospital for treatment against chlamydia psittaci pneumonia which was diagnosed by metagenomics next generation sequencing (mNGS). During the treatment period, chest imaging showed migratory infiltrates, which has been rarely described before.